Сучасні аспекти формування територіального розвитку столиці України та столичного мегаполісу - Новаковська, Ірина Олексіївна; Береза, Олександр Васильович (НУБіП України, 2023)
The issues of territorial development of the city of Kyiv and the capital metropolis have been considered. It has been determined that its current state was formed during the years 1957- 1988 and has remained stable for almost 35 years. The city operates in accordance with widely accepted principles of sustainable development based on the existing General Plan and urban land use and conservation programs developed for five-year periods (2001-2025). The prospective model of city planning takes into account the local association "Kyiv Agglomeration" that has been established. An analysis is conducted on the City Development Strategy until 2025 and the features of the existing General Plan. The issues related to the increasing role of land resources in satisfying the socio-economic needs of urban residents and in shaping a high-quality living space during the implementation of urban targeted land use and conservation programs are examined.
Keywords: територіальний розвиток; стратегії розвитку міста; охорона земель міста Києва; protection of lands of the city of Kyiv; Schutz des Landes der Stadt Kiew; Stadtentwicklungsstrategien; city ​​development strategies; territorial development; territoriale Entwicklung